FEDERAL AND REGIONAL REGULATION OF INNOVATION ACTIVITIES IN RUSSIA - Petrovich Garnov, Andrey; Alekseevna Prodanova, Natalia; Yuryevna Garnova, Victoria; Vladimirovna Shabaltina, Larisa; Ivanovna Zatsarinnaya, Elena (Revista Gênero e Interdisciplinaridade, 2020)
In the modern world of integration and globalization of world markets, the importance of innovation in the economy and development in the general system of government at the federal and regional levels has increased significantly. The complexity of the tasks being solved requires the development of a modern theoretical and methodological basis for regional management, the formation of adapted organizational and economic, financial and budgetary and other forms and tools for managing innovation and investment attractiveness. The main goal of the study is to reveal the peculiarities of the functioning of regional innovation systems, describe the indicators and features that determine the specifics of each regional innovation system, consider the main methodological approaches to the formation and functioning of regional innovation systems, disclose the essence and possibility of applying general theoretical principles and indicators of state statistical reporting to analyze the innovative position of regions.